Μοριακή και μορφολογική ταυτοποίηση ειδών του γένους Alternaria από καρπούς ροδιάς - Σόλωνος, Σόλωνας (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
"Black heart" or "heart rot" disease of pomegranate fruit, related to the genus Alternaria, has been reported causing significant qualitative and quantitative crop losses worldwide. The scope of the present study was the species identification of the Alternaria species involved in the "black heart" of pomegranates in Greece and Cyprus. Thus, during 2013, local orchards were surveyed and 82 fungal isolates of the genus Alternaria from Greece and Cyprus were collected from pomegranates expressing preharvest rot symptoms. Partial sequencing of the endopolygalacturonase (EndoPG) gene using the primers PG3 and PG2b, revealed that preharvest Alternaria pomegranate fruit rots were caused by the species Alternaria alternata, A. tenuissima, and A. arborescens. More specifically, 30 isolates were A.alternata, 19 A. tenuissima and 14 A. arborescens. The remaining 19 isolates were found to belong to the complex A. alternata/A. tenuissima and an accurate separation at the species level was not possible. In order to fulfill full identification the remaining isolates were characterized based on morphological characteristics and more specifically on their sporulation patterns. The combinatorial identification approach followed herein revealed that the predominant Alternaria species related to the 'black heart" of pomegranates was A. alternata with frequencies of 50 and 55.9% in Greece and Cyprus, respectively. The species A. tenuissima and A. arborescens followed at frequencies of 31.2% and 29.4% and 18.8% and 14.7% in Greece and Cyprus, respectively.
Keywords: Black heart disease; Heart rot disease; Pomegranate fruit; Genus Alternaria; Μύκητες; Καρπός ροδιάς; Ασθένεια "μαύρη καρδιά"; Ασθένεια "σήψη της καρδιάς"; Μοριακή μέθοδος; Μορφολογική ταυτοποίηση